Analysis of GSDMD-N abnormality promoting neutrophil NETs mediated RA disease through NLRP3-dependent pathway - Sang, Yali; Liu, Huiyang; Li, Bingle; Zhu, Lingyan; Wang, Yongfu; Bai, Li (Frontiers in Immunology, 2025)
IntroductionRheumatoid arthritis (RA) is characterized by persistent synovitis and progressive joint damage. Mounting evidence implicates neutrophil extracellular traps (NETs) formation (NETosis) in RA pathogenesis, yet the upstream regulatory nodes remain incompletely defined. We aimed to elucidate the role of the NLRP3 inflammasome in regulating GSDMD-dependent NETosis and to evaluate whether inhibiting NLRP3 or Gasdermin D (GSDMD) alleviates RA pathology.MethodsNeutrophils and synovial tissues from patients with RA and osteoarthritis (OA) were analyzed for NLRP3, GSDMD, and NET-related markers by immunofluorescence, Western blot, and qPCR. A collagen-induced arthritis (CIA) mouse model was used to test the effects of pharmacological inhibition of NLRP3 or blockade of GSDMD pore formation on joint swelling, bone destruction, and synovial inflammation. Transcriptomic sequencing was performed to identify differentially expressed genes following inhibition of GSDMD pore formation. Ionomycin was used to induce ROS-independent NETosis in vitro.ResultsThe RA group exhibited elevated NLRP3/GSDMD expression and increased NET markers relative to OA controls. In CIA mice, inhibition of NLRP3 or blockade of GSDMD pore formation mitigated joint swelling, reduced bone erosion, and attenuated synovial inflammation. Transcriptomic profiling identified 12 core genes—enriched for heat-shock proteins and histone variants—with significant differential expression after GSDMD pore inhibition. Ionomycin stimulation enhanced ROS-independent NET formation and was accompanied by increased NLRP3 expression and promoted cleavage of GSDMD into its active N-terminal fragment (GSDMD-N). Conversely, suppressing NLRP3 activation or preventing GSDMD pore formation effectively inhibited this process.DiscussionThese data position the NLRP3 inflammasome as a pivotal upstream regulator of GSDMD-dependent NETosis in RA. Targeting this axis—via inhibition of NLRP3 or blockade of GSDMD pore formation—ameliorates inflammatory joint pathology in vivo and constrains NETosis in vitro. Collectively, our findings support the NLRP3–GSDMD pathway as a promising therapeutic avenue for RA.